The naked communist : Cold War modernism and the politics of popular culture - Végső, Roland (Fordham University Press, 2013)
'The Naked Communist' argues that the political ideologies of modernity were fundamentally determined by four basic figures the world, the enemy, the secret, and the catastrophe.